Conceptual Design Interpretations, Mindset and Models - Andreasen, Mogens Myrup (Springer eBooks, 2015)
Maximising reader insights into the theory, models, methods and fundamental reasoning of design, this book addresses design activities in industrial settings, as well as the actors involved. This approach offers readers a new understanding of design activities and related functions, properties and dispositions. Presenting a ‘design mindset’ that seeks to empower students, researchers, and practitioners alike, it features a strong focus on how designers create new concepts to be developed into products, and how they generate new business and satisfy human needs.   Employing a multi-faceted perspective, the book supplies the reader with a comprehensive worldview of design in the form of a proposed model that will empower their activities as student, researcher or practitioner. We draw the reader into the core role of design conceptualisation for society, for the development of industry, for users and buyers of products, and for citizens in relation to public systems. The book also features original contributions related to exploration, conceptualisation and product synthesis.   Exploring both the power and limitations of formal design process models, methods, and tools viewed in the light of human ingenuity and cognition, the book develops a unique design mindset that adds human understanding to the list of methods and tools essential to design. This insight is distilled into useful mindset heuristics included throughout the book.